Rethinking stress in education: cortisol and DHEA-S biomarker outcomes of a mindset intervention - Langrafe Junior, Ari; Fernandes, Luiz Claudio; Peixoto, Evandro Moraes; Nishiyama, Anita (Frontiers in Behavioral Neuroscience, 2025)
ObjectiveTeacher stress is a global concern with significant consequences for health, performance, and educational quality. While most studies address stress as a harmful phenomenon, emerging evidence suggests that an individual’s mindset toward stress can influence both psychological and physiological outcomes. This study investigated whether a brief video-based mindset intervention could alter stress perception and modulate biological stress markers among public school teachers in Brazil.MethodsA randomized controlled trial was conducted with 63 teachers allocated into intervention (n = 32) and control (n = 31) groups. The intervention group received an 8-days series of short educational videos developed by Stanford University’s Mind and Body Lab, designed to promote a growth-oriented stress mindset. Measures included the Stress Mindset Measure (SMM), Perceived Stress Scale (PSS-10), Stroop Color Task, and salivary biomarkers (cortisol and DHEA-S). Data were collected at baseline, post-intervention, and 30-days follow-up. Analyses included repeated measures ANOVA and t-tests.ResultsThe intervention significantly improved stress mindset scores immediately after the intervention and at follow-up (p < 0.001; ε2 = 0.664), with no change in the control group. Cortisol concentrations decreased significantly in the intervention group post-intervention (p = 0.004; ε2 = 0.262), though the effect was not maintained after 30 days. No significant changes were observed in DHEA-S levels. Additionally, cognitive performance on the Stroop incongruent task improved significantly in the intervention group (p = 0.003; d = 0.565), suggesting enhanced executive functioning under stress.DiscussionThe findings support the effectiveness of a brief, low-cost intervention in shifting stress mindsets and producing acute physiological and cognitive benefits. However, the transient nature of the hormonal response underscores the need for sustained or complementary strategies to reinforce long-term stress resilience. This study highlights the value of mindset-based approaches in educational settings and their potential for improving teacher well-being through psychoneuroendocrinological mechanisms.